Nuclear Decay Rate Oscillations and a Gravity-Quantum Connection - T. Longo, Robert (New Trends in Physical Science Research Vol. 1, 2022)
This paper constructs a model to evaluate the hypothesis that the incompatibility between General Relativity and Quantum Mechanics is due to the different space-time geometries upon which each respective theory was built. An abstract field is envisioned as a way to transform coordinate variables of Euclidian geometry to coordinate variables in Riemann geometry, thereby linking Quantum Mecha- nics to General Relativity. The model is applied to an unexplained yearly rhythmic phenomenon of the nuclear decay count rate that is thought to be due to unknown emissions from the Sun. This work suggests the effect is due to gravitation, if so the planets must contribute. The Sun’s massive influence is eliminated by studying the yearly count rate variation when the Sun is at its perihelion. The measurements used in this study is a 15-year measurement of the nuclear decay of 226Ra.